ANALISIS HUBUNGAN SYSTEM USABILITY SCALE DENGAN DESKILLING PENGGUNA ADOBE PHOTOSHOP CC - Rinkapati Swatriani (Narada : Jurnal Desain dan Seni, 2018)
New features found in Adobe Photoshop CC software cause problems about usability. Because a modern technology that has some automatic function and default setting provides an opportunity to anyone to use that software without learn to operate or understand how it works. Therefore, this research was made for measure the degree of user convenience to Adobe Photoshop CC and the linkage between the ease of using Adobe Photoshop CC and the user’s helplessness. The methode used in this research is quantitative with SUS (System Usability Scale), developed by oleh John Brooke (1996). SUS contains 10 simple statements about the system and the answer be measured with Likert scale that organized from left to right 1 – strongly disagree, 2 – disagree, 3 – doubtful, 4 – agree, 5 – strongly agree